2013
DOI: 10.2298/tsci110327166a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of natural melt convection in cylindrical cavity with hot walls and cold bottom sink

Abstract: Numerical study of natural convection heat transfer and fluid flow in cylindrical cavity with hot walls and cold sink is conducted. Calculations are performed in terms of the cavity aspect ratio, the heat exchanger length and the thermo physical properties expressed via the Prandtl number and the Rayleigh number. Results are presented in the form of isotherms, streamlines, average Nusselt number and average bulk temperature for a range of Rayleigh number up to 106. It is observed that Rayleigh number and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In all cases, Prandtl number is fixed to 0.011 characterizing a silicon melt. According to Ahmanache and Zeraibi , the aspect ratio has no significant effect on fluid flow and heat transfer in such cavity then we limit our study to a single case of aspect ratio A = 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, Prandtl number is fixed to 0.011 characterizing a silicon melt. According to Ahmanache and Zeraibi , the aspect ratio has no significant effect on fluid flow and heat transfer in such cavity then we limit our study to a single case of aspect ratio A = 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmanache and Zeraibi have studied the effects of aspect ratio, exchanger length at various Rayleigh numbers (Ra = 10 3 ‐10 6 ) for material with Pr = 20 in a cylindrical HEM crucible. They observed that Rayleigh number and heat exchanger length influence fluid flow and heat transfer, whereas the cavity aspect ratio (A = 0.5, 1, 1.5 and 2) has no significant effects in such cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The dimensionless equations of vorticity transport, Poisson, and energy for the gas in the natural convection regime and the heat conduction equations for the enclosures and radiant energy source are [12,13,27]:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Studies of convective energy transfer regimes play an important role in science and engineering. Solutions of various natural convection problems in closed and semi-open cavities in non-conjugate [8][9][10][11][12][13][14] and conjugate [15][16][17][18] formulation are published. However, a special interest for practical applications represents investigation of jointly proceeding processes of conduction, convection, and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Raisi [Raisi (2016)] examined the natural convection in a square cavity filled with a non-Newtonian power-law fluid and used the numerical finite difference method based on the control volume formulation and SIMPLE algorithm. Certain studies have also been devoted to natural convection in other geometric configurations: Tzeng et al [Tzeng, Liou and Jou (2005)] considered a triangular enclosure, Basak et al [Basak, Roy, Singh et al (2009)] treated a trapezoid enclosure, while Ahmanache et al [Ahmanache and Zeraibi (2013); Alam, Rahman, Parvin et al 2016] examined a prismatic enclosure. In this first category, relating to natural convection all studies cited above show that if the sidewalls of the cavity are adiabatic, instabilities, loss of symmetry and bifurcation phenomena have been found to depend mainly on Rayleigh numbers, aspect ratio and vertex angles of the enclosure.…”
Section: Introductionmentioning
confidence: 99%